EVALUASI PENGELOLAAN BENDA BERHARGA ASAL MUATAN KAPAL YANG TENGGELAM DI JEPARA - , Jujun Kurniawan; , Dr. Widya Nayati, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is to evaluate the management process and policies that had applied on salvage activities of the Valuable Objects from Sunken Ships (Benda Berharga Asal Muatan Kapal yang Tenggelam/BMKT) in the Java Sea, located in the Mandalika Island water area, Jepara Regency, Central Java. This emphasized of this evaluation study is to ascertain possibillities of achievement of the management process that has been done, in order to improve and develop procedures for better/ideal management. The aspects that try to assert are the elements of management, involvement of stakeholders in the management, and the management mechanism that ever prevail. This research is expected to find a solution that can accommodate all parties, and then trying to reconstitut the working plan in order to optimize utilization, for the sustainable management of the Valuable Objects from Sunken Ships as archaeological resources in Jepara. The research was conducted using qualitative-evaluative method, which is try to understand and examine the execution of an activity, looking for feedback to improve implementation of activities, as well as to measure whether the purpose of the activity is reached. The results, showed that the management procedures of the Valuable Objects from Sunken Ship in Jepara has not yet been done completely. In addition, this management in Jepara also have some potentially causing a problem. The management strategy of the salvage and utilization activities in this Valuable Objects from Jeparaâs Sunken Ship is recommended to include the re identification of the artefact, ensuring the availability of legal protection that can protect the archaeological resources, preservation of artefact found, documenting in detail, as well as provide opportunities for the public to explore the archaeological resources.